Playing King - Berlova, Maria (Nordic Theatre Studies, 2018)
The Swedish King Gustav III ruled from 1771 to 1792. His departure to the Russian war in 1788 was staged as a grandiose spectacle. The King, who was also a playwright, made the day of his departure coincide with the symbolic date of June 23. This was the date that Gustav II Adolph (ruled 1611-32) went off to the Thirty Years' War in 1628. The parallel between Gustav III and the great Swedish warrior King was further emphasized by his costume made in the style of Gustav Adolph. In this article, the author analyzes Gustav III's departure to war as a theatrical event and explores the borders of theatrical events in the late eighteenth century. Gustav III's ceremonial departure is placed in the framework of Nikolai Evreinov's and Yuri Lotman's theories of theatricality which show how the King applied theatrical means to everyday life in order to theatricalize it, i.e. to make it spectacular and symbolic. By the atricalizing life Gustav III idealized his role of king and thus performed his power. Theatricalization of political life not only adorned life but it also significantly changed reality; the theatrical playing of the King entailed real consequences - Gustav III enacted his role of a monarch in a memorabl eway and achieved his political goals. The interaction between politics and theater is the main focus of the article. The author also explores the poetics of theatrical playing in politics. Obviously, the relation between the King-performer and his subjects-spectators was different from the usual actor-spectator relation in the traditional theater. During the communication of the King-performer and his subjects-spectators the political context was of significant importance; the main purpose of such communication was political propaganda. As a result of his ceremonial departure and, eventually, the theatricalization of war, the King succeded in becoming a national hero among the simple people, which proves the efficacy of theatrical means.